Assessment of the effectiveness and safety of ethosuximide in the treatment of abdominal pain related to irritable bowel syndrome – IBSET: protocol of a randomised, parallel, controlled, double-blind and multicentre trial. Issue 7 (18th July 2017) - Kerckhove, Nicolas; Scanzi, Julien; Pereira, Bruno; Ardid, Denis; Dapoigny, Michel
Abstract : Introduction: Irritable bowel syndrome (IBS) is characterised by the association of abdominal chronic pain with bowel habit disorders in the absence of identifiable organic disease. This is the first reason for consultation in gastroenterology, with an estimated prevalence of 10%–15% in industrialised countries. Although this is a benign gastrointestinal disease, its chronicity profoundly impacts the patient's quality of life and causes considerable health spending. Actual medical treatments are poorly efficient on IBS-related abdominal pain, making it a major public health concern. The mechanisms causing IBS symptoms are unknown. Recent studies have shown the involvement of T-type channel in abdominal pain. We aim to evaluate the therapeutic potential of ethosuximide, a T-type channel blocker, on the abdominal pain of patients presenting an IBS. Methods and analysis: The IBSET trial is a randomised, controlled, parallel, double-blind and multicentre study. It is the first clinical trial evaluating the efficacy and safety of ethosuximide on abdominal pain related to IBS. Adults with IBS that report significant abdominal pain (≥4/10) at least for 3 months will be included. 290 patients will be randomly assigned to receive either ethosuximide or placebo over 12 weeks after 1 week of run-in period. The primary endpoint is the rate of responders (pain reduction ≥30% and Subject Global Assessment of Relief score ≥4). The intensity of abdominal pain will be assessed by an 11-point Numerical Rating Scale before and after 12 weeks of treatment and the score of the Subject Global Assessment of Relief scale at the end of treatment. The secondary endpoints are the safety of ethosuximide, the intensity and features of IBS and quality of life. Ethics and dissemination: The study was approved by an independent medical ethics committee (CPP Sud-Est VI, Clermont-Ferrand, France). The results will be published in a peer-review journal and presented at international congresses. Trial registration number: NCT02973542; Pre-results.